Тheoretical aspects of modern geomorphogenesis (Journal of Geography and Environmental Management, 2016)
In the article the theoretical aspects of modern geomorphogenesis, given the description of the concepts of modern relief, tehnomorfogenez, tehnomorfosistemy
Keywords: modern relief; geomorphogenesis